Does integrated community case management (iCCM) target health inequities and treatment delays? Evidence from an analysis of Demographic and Health Surveys data from 21 countries in the period 2010 to 2018 - Winskill,P; Mousa,A; Oresanya,O; Counihan,H; Okell,L; Walker,P (Journal of Global Health, 2021)
BackgroundIntegrated community case management (iCCM) is a programme that can, via community health workers (CHWs), increase access to timely and essential treatments for children. As well as improving treatment coverage, iCCM has an additional equity-focus with the aim of targetingunderserved populations. To assess the success of iCCM programmes it is important that we understand the contribution they are making to equitable health coverage.MethodsWe analysed demographic and health survey data from 21 countries over 9 years to assess evidence and evaluate iCCM programmes. We summarise the contribution CHWs are making relative to other healthcare provider groups and what treatment combinations CHWs are commonly prescribing. We assessed the ability of CHWs to target treatment delays and health inequities by evaluating time to treatment following fever onset and relationships between CHWs and wealth, rurality and remoteness.ResultsThere was good evidence that CHWs are being successfully targeted to improve inequities in healthcare coverage. There is a larger contribution of CHWs in areas with higher poverty, rurality and remoteness. In six surveys CHWs were associated with significantly shorter average timebetween fever onset and advice or treatment seeking, whilst in one they were associated with significantly longer times. In areas with active CHW programmes, the contribution of CHWs relative to other healthcare provider groups varied between 11% to 45% of treatment visits. The distribution of types of treatment provided by CHWs was also very variable between countries.ConclusionsThe success of an iCCM programme depends not only on increasing treatment coverage but addressing inequities in access to timely healthcare. Whilst much work is still needed to attain universal healthcare targets, and despite incomplete data, there is evidence that iCCM is successfully addressing treatment delays and targeting underserved populations.